2018
DOI: 10.1371/journal.pone.0194583
|View full text |Cite
|
Sign up to set email alerts
|

RNA secondary structure prediction with pseudoknots: Contribution of algorithm versus energy model

Abstract: MotivationRNA is a biopolymer with various applications inside the cell and in biotechnology. Structure of an RNA molecule mainly determines its function and is essential to guide nanostructure design. Since experimental structure determination is time-consuming and expensive, accurate computational prediction of RNA structure is of great importance. Prediction of RNA secondary structure is relatively simpler than its tertiary structure and provides information about its tertiary structure, therefore, RNA seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Given the role of the leader-repeat stem-loop in prioritizing immune defense for the S. pyogenes CRISPR-Cas9 system, we hypothesized that this mechanism would exist in many other CRISPR-Cas9 systems. The predicted interactions between the protruding loops of the leaderrepeat stem-loop and the second repeat for the S. pyogenes system are likely weaker, transient, and dependent on co-transcriptional folding 38 . However, the extensive stem formed between the leader RNA and first repeat offers a key feature that could be systematically predicted across CRISPR-Cas9 systems.…”
Section: Leader-repeat Stem-loops Found Across Crispr-cas9 Systemsmentioning
confidence: 99%
“…Given the role of the leader-repeat stem-loop in prioritizing immune defense for the S. pyogenes CRISPR-Cas9 system, we hypothesized that this mechanism would exist in many other CRISPR-Cas9 systems. The predicted interactions between the protruding loops of the leaderrepeat stem-loop and the second repeat for the S. pyogenes system are likely weaker, transient, and dependent on co-transcriptional folding 38 . However, the extensive stem formed between the leader RNA and first repeat offers a key feature that could be systematically predicted across CRISPR-Cas9 systems.…”
Section: Leader-repeat Stem-loops Found Across Crispr-cas9 Systemsmentioning
confidence: 99%
“…CCJ (Chen et al., 2009) and its efficient implementation, Knotty (Jabbari et al., 2018), are among the best‐performing MFE algorithms for prediction of pseudoknotted structures. These methods can handle kissing hairpin structures with arbitrary nested (possibly pseudoknotted) substructures as well as chains of four interleaved bands (or the ABACBDCD motif).…”
Section: Methodsmentioning
confidence: 99%
“…We say an algorithm can handle a structure if it is in the class of structures the algorithm can predict. We note that even if a structure is handled by an algorithm, the algorithm may not predict the structure, as correct structure prediction depends on the underlying energy model as well as the class of structures an algorithm can handle (Jabbari, Wark, & Montemagno, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the accuracy of MFE RNA secondary structure prediction decreases with sequence length both for pseudoknot-free [ 35 ] and pseudoknotted structures [ 36 ]. This has motivated research on incorporating available data (e.g.…”
Section: Rna Secondary Structurementioning
confidence: 99%